THE IMPLEMENTATION OF COGNITIVE ACADEMIC LANGUAGE LEARNING STRATEGIES (CALLS) TO HELP THE STUDENTS IN RECOGNIZING THE LEXICAL CONSTRAINTS ON THE STUDENTS TRANSLATION - Astuty, Diah (E-Link Journal, 2016)
his study aims to describe the sorts of lexical constraints that appeared on the students translation when translating some source language texts into some target language texts. The competence of linguistic fields that the students have acquired is in the fact assumed to be inadequate and it can cause the lexical constraints.Keywords: CALLS, lexical constraints,source language text,target language text